Grounded in heaven : recentering Christian hope and life on God - Allen, Michael, 1981- (Grand Rapids, MI. W.B. Eerdmans Publishing Company, 2018)
Eschatology and ethics are joined at the hip, says Michael Allen, and both need theocentric reorientation. In Grounded in Heaven Allen retrieves the traditional concept of the beatific vision and seeks to bring Christ back into the heart of our theology and our lives on earth. Responding to the earthly-mindedness of much recent theology, Allen places his focus on God and the heavenly future while also appreciating ways in which the Reformed tradition provides a unique angle on broadly catholic concerns. Reaching back to classical ethics as well as its reformation by Calvin and other Reformed theologians, Grounded in Heaven offers a distinctly Protestant account of the ascetical calling to be heavenly-minded and to deny one's self
Includes bibliographical references and indexes
Keywords: Desire for God; Beatific vision; Spiritual life -- Christianity; Hope -- Religious aspects -- Christianity